Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2014
DOI: 10.1145/2556288.2557165
|View full text |Cite
|
Sign up to set email alerts
|

Under pressure

Abstract: Recognizing when computer users are stressed can help reduce their frustration and prevent a large variety of negative health conditions associated with chronic stress. However, measuring stress non-invasively and continuously at work remains an open challenge. This work explores the possibility of using a pressure-sensitive keyboard and a capacitive mouse to discriminate between stressful and relaxed conditions in a laboratory study. During a 30-minute session, 24 participants performed several computerized t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(30 citation statements)
references
References 34 publications
1
22
0
1
Order By: Relevance
“…Regarding CSF measurements, they are intrusive, costly and slow methods of analysis [300]. Furthermore, all of these current tests, are "usually administered in a physician's office or a rehabilitation facility, causing inconvenience for the patient, using valuable healthcare resources, making frequent monitoring unrealistic" [296] and therefore, precluding an early diagnosis.…”
Section: Critical Reviewmentioning
confidence: 99%
“…Regarding CSF measurements, they are intrusive, costly and slow methods of analysis [300]. Furthermore, all of these current tests, are "usually administered in a physician's office or a rehabilitation facility, causing inconvenience for the patient, using valuable healthcare resources, making frequent monitoring unrealistic" [296] and therefore, precluding an early diagnosis.…”
Section: Critical Reviewmentioning
confidence: 99%
“…Another approach to stress detection has been presented in [15] where the possibility of using a pressure-sensitive keyboard and a capacitive mouse to discriminate between stressful and relaxed conditions was investigated. It turned out that under stress the typing pressure increased and more contact with the surface of mouse was observed.…”
Section: Related Workmentioning
confidence: 99%
“…visual [5], depth [6], audio [7], textual [8], physiological [9], standard input devices [10]- [15] or multi-modal input [16]. Not all of them seem practical in any situation, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Although subjective reporting (first-or third-person) comes with several limitations, such as self-deception and memory-biases, it offers the most direct and popular approach to the annotation of subjective constructs. Thus, quantitative reports via questionnaires provide unique properties for evaluating the capacity of interactive systems (Bardram et al, 2013;Chen et al, 2014) and for constructing computational models of reported user states (Hernandez et al, 2014).…”
Section: Introductionmentioning
confidence: 99%